Fuzzy and ANN based variable gain PI controllers for STAT COM - Morris, , S; Dash,, PK; Basu, , KP (2005)
in this paper a closed form variable structure fuzzy PI controller is proposed for STATCOM to stabilize the electro-mechanical oscillations of a power system. The function based fuzzy controller uses Takagi-Sugeno-Kang (TSK) scheme with just two or three rules and generates the proportional action which by one-to-one or one-to-two mappings can generate a variable gain nonlinear PI controller. Unlike the two input fuzzy controller, one input function based scheme dispenses the gain dependency of the proportional or integral gains and generates independent control actions. Further the parameters of the function based controller have been tuned by an ANN based approach using an extended Kalmann filter algorithm. Numerical test results on a 2-area 4-machine 12-bus power system with a STATCOM on the tieline between the areas confirm the efficacy of the new approach in damping local mode and nonlinear oscillations.